Au croisement de l’histoire culturelle et des sciences de l’information et de la communication. Une approche transdisciplinaire des transferts culturels dans les Alpes Occidentales tardo-médiévales - Marianne Cailloux (Diasporas: Circulations, Migrations, Histoire)
This article ponders about the new orientations of the cultural history of images of the medieval and modern periods. The modalities of mediation, of processing by dynamics and flows lead to reinterpret the analysis of the image as a global object of study, following Hans Belting’s works, and by summoning authors such as Yves Jeanneret. It is a question of observing how the theories and the concepts of the sciences of the information and communication potentially allow an interdisciplinary opening in the study of the cultural transfers, here through examples from the Western Alps.